Experimental study on the influence of content and fineness of fly ash on the mechanical properties of grouting slurries - Hua Jiang; Handong Zhang; Xiaoyan Zhang; Jinxun Zhang; Yusheng Jiang (Deep Underground Science and Engineering)
Abstract Excavation gaps around the front shield can be generated during shield construction, resulting in significant ground settlement. Traditional synchronous grouting slurries are unsuitable for filling these gaps during tunneling under existing subway lines. To address this issue, experiments are conducted on mix characteristics and hardening properties of slurries with variations in fineness and contents of fly ash. The experimental and computed tomography scan results yield the following findings: (1) fly ash with high fineness can effectively reduce the early strength of slurries and enhance their injectability. This improves the filling effect on micropores in the slurry and ultimately enhances the final hardening strength. (2) Fineness of fly ash controls the process of slurry hydration. The higher the fineness of fly ash, the more visible the exothermic hydration of slurry and the earlier the highest temperature peak appears. (3) Fly ash with high fineness can effectively increase the density and consolidation rate of slurries, resulting in greater improvement in slurry strength, particularly when the ratio of fly ash to cement (mf/mc) is 0.75. (4) Fly ash with high fineness can effectively decrease the likelihood of appearance of pores in the slurry, optimize the pore structure, and enhance the strength of slurries after consolidation.